The interaction between Caenorhabditis elegans and the bacterial pathogen Stenotrophomonas maltophilia - White, Corin Vashoun (Kansas State University, 2015)
Nematodes play an important role in various habitats where numerous factors serve to shape their communities. One such factor is the potentially pathogenic nematode-prey interaction. This project is focused on the elucidation of the genes that the bacterivorous nematode Caenorhabditis elegans employs to respond to the emerging nosocomial bacterial pathogen Stenotrophomonas maltophilia. A virulent S. maltophilia strain JCMS requires the action of several C. elegans conserved innate immune pathways that serve to protect the nematode from other pathogenic bacteria. However, insulin-like DAF-2/16 signaling pathway mutants that are typically pathogen resistant are susceptible to JCMS, and several DAF-2/16 regulated genes are not significantly differentially expressed between JCMS and avirulent E. coli OP50. We have determined the complete set of mRNA transcripts under different bacterial treatments to identify genes that might explain this JCMS specific DAF-2/16 pathway evasion. The identified set included 438 differentially expressed transcripts among pairwise comparisons of wild-type nematodes fed OP50, JCMS or avirulent S. maltophilia K279a. Candidate genes were nominated from this list of differentially expressed genes using a probabilistic functional connection model. Six of seven genes that were highly connected within a gene network generated from this model showed a significant effect on nematode survival by mutation. Of these genes, C48B4.1, mpk-2, cpr-4, clec-67 and lys-6 are needed for combating JCMS, while dod-22 was solely involved in K279a response. Only dod-22 had a documented role in innate immunity, which merits our approach in the identification of gene candidates. To a lesser extent, we have also focused on the identification of virulence factors and the mode of action employed by S. maltophilia. JCMS virulence requires rpfF, xps and involves living bacteria that accumulate in the intestinal lumen. Additionally, the bacterial secretion encoding genes cs, p773, p1176, pi1y1 and xdi are involved in JCMS evasion of daf-2. In summary, we have discovered a novel host-pathogen interaction between C. elegans and S. maltophilia JCMS, revealed genes that are involved in each partner of the interaction, and established a new animal model for the study of S. maltophilia mode of action.
Keywords: Host pathogen interaction; Transcriptomics; C. elegans; S. maltophilia; Biology (0306)